Hijau Atau Merah Paspor Kita Tetap Lemah: Diskursus Kekuatan Paspor - Anggara, Hetri Pima (Sekretariat Jenderal DPR RI, 2024)
On August 17, 2024, Indonesia released a new passport design themed on the archipelago'sfabrics. The public felt that strengthening the power of Indonesia's passport was more importantthan changing the design. The public even compared the power of Indonesia's passport, whichis weaker than those of neighboring countries. In the discourse of the passport's power, it isunclear whether the ‘power’ in question refers to the passport as a document or the countrythat issued the passport. This research aims to explore whether the passport's power is directlyproportional to the material power of the issuing country and criticize the meaning of thepassport's power. To reveal the meaning of passport power, this paper uses the concept ofpower in a constructivist perspective, which is then compared with material power attributes.Comparation reveals that the material power of a country does not always reflect the powerof its passport. Indonesia's passport is weaker because the visa granting policy is based onideational aspects in bilateral interactions between countries and not solely on the country'smaterial capabilities. The passport power narrative has a political dimension by benefitingcertain parties in the discourse. The word ‘power’ will justify hegemonic structures and reinforcediscrimination against low-ranking countries.